Revitalizing Arabic Language Learning: the impact of 'Kaifa Haluka' bilingual comics - Mohd Saad, Muhammad Luqman Ibnul Hakim; Badaruddın, Mohammed Iqbal; Nik Hashim, Nik Ahmad Kamal Juhari; Mohamed, Mohd Sollah; Tengku Abd Aziz, Tengku Mohd Farid (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Traditional Arabic textbooks often struggle to engage students, which can lead to decreased motivation and focus during learning activities. In response, the bilingual comic series 'Kaifa Haluka' (KH) has been created as an innovative resource to enhance the Arabic language learning experience. KH differentiates itself from conventional materials by integrating technology, including QR codes, videos, vibrant illustrations, Arabic dialogue transcriptions, and vocabulary support. This initiative has gained recognition at various conferences, been featured in academic journals, and achieved commercial success, earning accolades for its intellectual property. The uniqueness of KH is not only in its technological features but also in its ability to refresh the learning process through interactive formats. KH aims to facilitate significant advancements in both societal and economic realms. By transforming Arabic language education with engaging bilingual comics, it has the potential to promote linguistic diversity and spark students' interest. Economically, the successful launch of KH could foster growth by creating new entrepreneurial opportunities. Research indicates that KH has a positive impact on students' achievements in learning Arabic. Feedback from students at UiTM Kelantan highlights their recognition of KH as an effective educational tool that supports their journey in mastering the Arabic language.